2016
DOI: 10.3389/fncel.2016.00056
|View full text |Cite
|
Sign up to set email alerts
|

Implications of MMP9 for Blood Brain Barrier Disruption and Hemorrhagic Transformation Following Ischemic Stroke

Abstract: Numerous studies have documented increases in matrix metalloproteinases (MMPs), specifically MMP-9 levels following stroke, with such perturbations associated with disruption of the blood brain barrier (BBB), increased risk of hemorrhagic complications, and worsened outcome. Despite this, controversy remains as to which cells release MMP-9 at the normal and pathological BBB, with even less clarity in the context of stroke. This may be further complicated by the influence of tissue plasminogen activator (tPA) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
298
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 381 publications
(310 citation statements)
references
References 132 publications
(244 reference statements)
9
298
3
Order By: Relevance
“…MMP-9 and neutrophil levels are elevated in the cerebrospinal fluid as well. Since rtPA itself promotes neutrophil degranulation, a peak of MMP-9 elevation can be detected 30 minutes after rtPA administration as well [105][106][107].…”
Section: Mmp-9 Levelmentioning
confidence: 99%
“…MMP-9 and neutrophil levels are elevated in the cerebrospinal fluid as well. Since rtPA itself promotes neutrophil degranulation, a peak of MMP-9 elevation can be detected 30 minutes after rtPA administration as well [105][106][107].…”
Section: Mmp-9 Levelmentioning
confidence: 99%
“…20) As a deleterious effect of tissue-type plasminogen activator (t-PA) which is a therapeutic drug for thrombus, hemorrhagic transformation by BBB disruption has been shown. 3,21) Abu Fanne et al 22) suggested that inhibiting t-PA improved brain tissue damage, edema, and mortality caused by increased BBB permeability in thromboembolic stroke rats. MMPs and VEGFs are involved in BBB disruption by t-PA.…”
Section: Hemorrhagementioning
confidence: 99%
“…3,13) Cerebral hemorrhage is a lethal condition, which results in sudden death, paralysis of the extremities, and cognitive dysfunctions. Hemorrhage results from a fracture of microvessels by cerebral contusions.…”
Section: Hemorrhagementioning
confidence: 99%
See 2 more Smart Citations